Evaluation of antimicrobial activity of root extract of Asclepias curassavica - C, Hemavani; B, Thippeswamy (Recent Research in Science and Technology, 2012)
The plants belonging to the Asclepiadaceae family has very high medicinal property. Asclepias curassavica is one such plant which comes under Asclepiadaceae family. In the present study the effect ofÂ  plant root extract of different solvents were screened against three bacteria and three fungi for their level of antimicrobial potential.To determine the compounds present that may produce an inhibitory effect on different classes of bacteria and fungi. Thin layer chromatography was used to assay for the compounds present and further these compounds were eluted through Column Chromatography.The crude extracts of petroleum ether, chloroform and methanol and two pure fractions obtained from methanol extract were tested for their antimicrobial property. The crude extract of chloroform was effective against Pseudomonas solanacearum and Escherichia coli than other extracts. The crude extract of methanol was effective against Clavibacter michiganense than other extracts. Compound 1 of methanol extract is effective than compound 2 against Pseudomonas solanacearum and compound 2 is effective than compound 1 against Clavibacter michiganense and Escherichia coli. The crude extract of chloroform was more effective against Aspergillus niger than Helminthosporium oryzae and Fusarium oxysporum. Whereas the petroleum ether and methanol extract has no antifungal property.